Communication between patients and health care professionals about opioid medications - Tanvee Thakur; Meredith Frey; Betty Chewning (Elsevier, 2021)
Prescription opioids contribute to 40% of opioid overdose deaths in the United States. Healthcare professionals (HCPs) play an important role in mitigating the prescription opioid epidemic by appropriate opioid prescribing and patient education. Yet, little empirical literature addresses pharmacist (and other HCP) communication with patients related to risks of opioid use associated with dependence, misuse, and overdose. Nor is there much research on the barriers and facilitators which affect whether and how much opioid-related information is discussed. This commentary, based on an extensive literature search, seeks to inform future communication, education, and research agendas by describing (1) topics commonly discussed or excluded from opioid medication counseling, (2) patient and HCP perceptions regarding opioid medication communication, and (3) barriers and facilitators to opioid risk communication. Based on this literature, recommendations are provided for opioid counseling practices, pharmacist education, and research agendas.